Els exvots en la taulelleria valenciana dels segles XVIII i XIX. - BUENAVENTURA, BEATRIU NAVARRO; CEBRIÁN MOLINA, JOSEP LLUÍS (Scripta, 2024)
We study the votive offerings painted on tiles from the 18th and 19th centuries. This ceramic typology is analyzed based on the works preserved in the sanctuary of castle of Cullera and some panels on public roads or inside homes. We also identify the authorship of some the painters who worked in the factories of the city of València: Mestre de Noguera, Valentí Garcés, Vicent Camarlenc, Joan Ortiz, Mestre de Santa Anna and Miquel Mollà.